2011
DOI: 10.1111/j.1365-2753.2011.01705.x
|View full text |Cite
|
Sign up to set email alerts
|

Reducing interrater variability and improving health care: a meta‐analytical review

Abstract: On average, although all types of interventions are effective, improving the diagnostic instrument seems to be the most effective. Especially when highly technical instruments were concerned, improvement proved to be very effective (β = 0.52). Because instrumental variables constitute a major source of error, improving the instrument is an important approach. However, this review offers solid arguments that can complement the literature and practice, with a focus on training the user of the instrument.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 65 publications
(13 reference statements)
0
31
1
Order By: Relevance
“…Here, efforts were made to enhance the agreement on the HCT-CI scoring by both improving the instrument (the comorbidity coding tool) and training the evaluators (the methodology and the Web-based application). 32,41 The IRR was lowest (Kw, 0.433) when scores were compared between a single evaluator and multiple untrained evaluators in the clinic, suggesting the need for a training program to prepare experienced comorbidity evaluators at different institutions.…”
Section: Discussionmentioning
confidence: 99%
“…Here, efforts were made to enhance the agreement on the HCT-CI scoring by both improving the instrument (the comorbidity coding tool) and training the evaluators (the methodology and the Web-based application). 32,41 The IRR was lowest (Kw, 0.433) when scores were compared between a single evaluator and multiple untrained evaluators in the clinic, suggesting the need for a training program to prepare experienced comorbidity evaluators at different institutions.…”
Section: Discussionmentioning
confidence: 99%
“…Interrater agreement and test‐retest agreement for all raters were at least substantial, supporting the stability of UMCT‐KE and UMCT‐KF ratings. Use of a well‐defined testing protocol and standardized instructions, and sufficient rater training are known to contribute to dependable results in reliability studies (Mong et al., 2010; Tuijin et al., 2012). However, wide confidence intervals with most of the lower limits extending down to moderate levels imply that further enhancements in test procedures and/or rater training may be needed.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies show that the training of professionals, improving diagnostic instruments or methodologies, and a combination of both training and methodology play significant roles in greater reliability 19 . Also, in TCM, two studies in patients with irritable bowel syndrome and rheumatoid arthritis demonstrated an improvement in the level of reliability with incorporation of a training phase in the study 20, 21.…”
Section: Discussionmentioning
confidence: 99%